A comparison of prognostic performance of perioperative inflammation markers in surgical resection for hepatocellular carcinoma. Issue 6 (2nd June 2021) - Wu, Hsiang-Ling; Kuo, Hsien-Cheng; Li, Chun-Cheng; Wu, Yu-Ming; Lin, Shih-Pin; Chang, Kuang-Yi; Hou, Ming-Chih; Tsou, Mei-Yung; Cherng, Yih-Giun; Chen, Jui-Tai; Tai, Ying-Hsuan
Abstract : Background: Systemic inflammation correlates closely with tumor invasion and may predict survival in cancer patients. We aimed to compare the prognostic value of various inflammation-based markers in patients with hepatocellular carcinoma. Methods: We consecutively enrolled 1450 patients with primary hepatocellular carcinoma undergoing surgical resection at the medical center between 2005 and 2016 and assessed them through September 2018. Prognostic nutritional index, neutrophil-to-lymphocyte ratio, and platelet-to-lymphocyte ratio along with their perioperative dynamic changes were analyzed regarding their predictive ability of postoperative disease-free survival and overall survival. We calculated the adjusted hazard ratio (HR) and 95% CI of the association between inflammation-based markers and survival using multiple Cox proportional hazards models. Youden's index of receiver operating characteristics curves was used to determine optimal cut-off points. Results: Prognostic nutritional index was an independent predictor for both disease-free survival (<50.87 vs ≥50.87, HR: 1.274, 95% CI, 1.071–1.517, p = 0.007) and overall survival (<46.65 vs ≥46.65, HR: 1.420, 95% CI, 1.096–1.842, p = 0.008). Besides, the relative change of neutrophil-to-lymphocyte ratio predicted overall survival (<277% vs ≥277%, HR: 1.634, 95% CI, 1.266–2.110, p < 0.001). Combination of both markers offered better prognostic performance for overall survival than either alone. Body mass index, liver cirrhosis, chronic kidney disease, and tumor diameter were significantly associated with both markers. Conclusion: Prognostic nutritional index and perioperative relative change of neutrophil-to-lymphocyte ratio independently predict postoperative survival in patients undergoing surgical resection of hepatocellular carcinoma. These results provided important evidence for risk stratification and individualized anti-cancer therapy.